Creative Science Learning Model for Early Childhood in Palangka Raya - Irmawati, Irmawati; Darmiyati, Darmiyati; Asniwati, Asniwati (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop a science learning model that can improve the creativity of early childhood (Early Childhood). The study was conducted in two Early Childhood Education institutions, namely TK Negeri Pembina Pahandut and TK Rajawali Sakti in Palangka Raya City. A qualitative approach with a multi-case study design was used to explore the implementation process, assessment models, and supporting and inhibiting factors for the development of creativity through science. The results of the study indicate that the implementation of project-based learning, exploration, experiments, and games has a positive impact on children's cognitive, affective, and psychomotor aspects. The implications of this study encourage the need to strengthen teacher training and provide creative science learning facilities in Early Childhood Education.